A CRISPR/Cas9-riboswitch-Based Method for Downregulation of Gene Expression in Trypanosoma cruzi - Lander, Noelia; Cruz-Bustos, Teresa; Docampo, Roberto (Frontiers in Cellular and Infection Microbiology, 2020)
ABSTRACT. Few genetic tools were available to work with Trypanosoma cruzi until the recent introduction of the CRISPR/Cas9 technique for gene knockout, gene knock-in, gene complementation, and endogenous gene tagging. Riboswitches are naturally occurring selfcleaving RNAs (ribozymes) that can be ligand-activated. Results from our laboratory recently demonstrated the usefulness of the glmS ribozyme from Bacillus subtilis, which has been shown to control reporter gene expression in response to exogenous glucosamine, for gene silencing in Trypanosoma brucei. In this work we used the CRISPR/Cas9 system for endogenously tagging T. cruzi glycoprotein 72 (TcGP72) and vacuolar proton pyrophosphatase (TcVP1) with the active (glmS) or inactive (M9) ribozyme. Gene tagging was confirmed by PCR and protein downregulation was verified by western blot analyses. Further phenotypic characterization was performed by immunofluorescence analysis and quantification of growth in vitro. Our results indicate that the method was successful in silencing the expression of both genes without the need of glucosamine in the medium, suggesting that T. cruzi produces enough levels of endogenous glucosamine 6-phosphate to stimulate the glmS ribozyme activity under normal growth conditions. This method could be useful to obtain knockdowns of essential genes in T. cruzi and to validate potential drug targets in this parasite.